IDENTIFICATION OF Escherichia coli BACTERIA IN QUAIL EGGS THAT FOR SALE IN THE CENTRAL MARKET OF THE CITY OF GORONTALO - Regitacahyanisauring Gita; Syam S. Kumaji; Erfan AR. Lainjong (Journal of Health, Technology and Science (JHTS), 2021)
Eggs are one of the animal products that come from poultry and have been known as a source of high quality protein food. From the many eggs we know, one of the eggs that comes from poultry is quail eggs. Quail eggs have complete nutritional content ranging from protein, fat, vitamins and minerals. Even so, quail eggs are also animal food that is easily decreased in quality due to bacterial contamination, contamination of quail eggs by bacteria can affect the quality of the contents of the eggs, bacteria that cause egg contamination, one of which is Escherichia coli. This study aims to determine the presence of Escherichia coli bacteria in quail eggs that are sold in the central market of Gorontalo city. The research method used is descriptive research type with a quantitative research approach, cross sectional research design, a sampling place for the central market of Gorontalo City and a place for researching samples of the Microbiology Laboratory of Gorontalo State University, the number of samples used was 30 samples of quail eggs. Quail eggs were positive for Escherichia coli bacteria with a percentage of 6.7%, and negative egg yields from Escherichia coli bacteria were 28 or 93.3%. It can be concluded that from 30 samples of quail eggs there were 2 quail eggs that were positive for Escherichia coli bacteria, the bacteria contamination factor in eggs was influenced by external factors. Environmental sanitation conditions were not clean, egg storage temperature, egg storage time,